(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The article examines the issues of socio-pedagogical cooperation of families, communities and educational institutions in educating young people in New Uzbekistan, a comparative analysis with the experience of foreign countries, as well as the research work of our scientists who have made significant contributions to youth education in the Republic of Uzbekistan. the results of the comparative study were reflected. Ways to improve the socio-pedagogical cooperation of families, communities and educational institutions, the results of experiments, the results of organized seminars and trainings, suggestions, recommendations and conclusions are described.